Tanah tak Bertuan: Volatilitas dan Stabilitas Elektoral di Jawa Barat Pasca Ode Baru - Permana, Panji Anugrah (Journal of Politics and Policy, 2024)
The changing power of political parties is one of the most important phenomena studied in democratic political systems. It can shed light on the extent to which political parties are connected to voters, the strengthening or weakening of party institutionalisation, the influence of personalities in politics, the influence of electoral and party institutional design, and so on. Studies on political party change (electoral volatility and stability) have been conducted comparatively, and some studies are conducted by looking at the national context of Indonesia. However, while studies have been conducted on these issues at the local level, they remain overlooked. This article fills this gap by presenting a description and analysis of electoral volatility and stability in West Java in the post-New Order era. Using the theoretical framework of electoral volatility and stability as well as the theory of party system institutionalisation (PSI), this study proposes three findings: high party turnover; higher electoral volatility in West Java compared to national electoral volatility; more competitive political party competition at the district/city level in West Java. The findings on electoral volatility, stability and competition are influenced by the restrictions of political party regulations, which have an impact on the decreasing number of political parties in elections, the personalisation of politics and the presidentialisation of politics, as well as the historical roots of the old-established parties that have been entrenched since the New Order era.